Religiosity and Sexual Initiation Among Hispanic Adolescents: The Role of Sexual Attitudes - Calatrava, Maria; Beltramo, Carlos; Osorio, Alfonso; Rodríguez-González, Martiño; De Irala, Jokin; Lopez-del Burgo, Cristina (Frontiers in Psychology, 2021)
Introduction: Religiosity and sexuality present numerous interconnections. Little is known regarding the specific causal pathways between each religiosity dimension and sexual behavior. The objectives of this study were (1) to explore the relationship between religiosity (measured through attendance at religious services, salience, and prayer) and sexual initiation in adolescents and (2) to establish the role of sexual permissiveness as mediator of the impact produced by religiosity in sexual initiation. Methods: This study analyzes data from an ongoing school-based international study examining what young people feel and think about relationships, love, and sexuality. An anonymous, self-administered online questionnaire was developed in Spanish. A total of 4,366 students, aged 14-18, completed the questionnaire. A final sample of 2,919 questionnaires was analyzed. Two unconditional logistic regression models were fit with religiosity variables and possible confounders as independent variables (with and without permissiveness respectively). The dependent variable was sexual initiation. A final structural equation model was fit to further understand the results. Results: Our study highlights that, in predominantly Catholic and Spanish-speaking countries, the fact of attending church and praying may greatly contribute to adolescents’ postponing sexual relations during adolescence, even independently of their opinions on sexual permissiveness. Conversely, the effect of salience on sexual initiation seems to be fostered only through the mediation of sexual permissiveness. Our findings point to an indirect effect of the three religiosity dimensions (and in particular, religious salience) through permissive attitudes. Conclusion: Religiosity could be a relevant factor to explain sexual initiation during adolescence.